Highly diastereoselective electrophilic fluorination of cyclic syn-beta-hydroxysilanes - Purser, S; Wilson, C; Moore, P; Gouverneur, V (2007)
A synthesis of enantioenriched fluorinated carbocycles has been developed combining a sequential enantioselective silylallylboration-ring-closing metathesis with a highly diastereoselective electrophilic fluorination. © Georg Thieme Verlag Stuttgart.